Analisis Quality Of Service pada Jaringan Internet di Universitas Sariputra Indonesia Tomohon - NADYA VERONA VIANI KAMASI (INTEK : Jurnal Informatika dan Teknologi Informasi, 2021)
Technology has developed very rapidly in recent years, including the internet. Internet is not only used in big cities but also to remote villages. The internet is also important in schools and colleges, one of which is Universitas Sariputra Indonesia Tomohon. The availability of good internet service then becomes an important issue. To find out the quality of existing internet network services, testing can be done with an analysis of the Quality of Service. Measurement of Quality of Service can be performed by QoS parameters, namely bandwidth, delay, packet loss, and throughput. This research was conducted using the action research method which aims to determine the quality of network services at Universitas Sariputra Indonesia Tomohon.